Pemetaan Spasial Kadar Kobal pada Endapan Laterit dengan Metode Ordinary Cokriging dan Inverse Distance Weighting: Spatial Mapping of Cobalt Content in Laterite Deposits Using Ordinary Cokriging Method and Inverse Distance Weighting - Hendro Purnomo; Shilvyanora Aprilia Rande; Rizqi Prastowo (LPPM Universitas Mataram, 2022)
Cobalt is a metallic element that can be found in laterite deposits with varying concentration in each lithology zone. Objective of this study was to compare the performance of the ordinary cokriging (OCK) and inverse distance weighting (IDW) in mapping the cobalt content of laterite deposits. Cross variogram analysis used the covariable Ni and Fe, and the selection of the variogram model used the residual sum of square parameter. The IDW interpolation process uses power 1 and 2. The determination of the best method is based on the mean error parameter, and the root mean square error. Meanwhile, to determine the accuracy of the OCK estimation results, the root mean square standardized prediction error is used. The study indicates that the performance of the OCK interpolation is better than IDW, with overestimated predictions. The results of OCK interpolation showed that the distribution of 0.1-0.18% cobalt spread in the northern part and narrowed in the southern part of the study area.